A Comparative Study of Alkaline Hydrolysis of Ethyl Acetate Using Design of Experiments - Afzal Ahmad; Muhammad Imran Ahmad; Muhammad Younas; Hayat Khan; Mansoor ul Hassan Shah (Iranian Journal of Chemistry & Chemical Engineering, 2013)
Alkaline hydrolysis of ethyl acetate is essentially an irreversible and second order reaction. Industrial importance of the reaction product, sodium acetate, necessitate for process improvement in terms of maximum conversion and economical usage of raw materials. Statistical design of experiments was utilized to enhance conversion in both batch and plug flow reactors.A full two level factorial design was used to screen out insignificant factors through analysis of variance followed by examining the significant factors in face-centered central composite design. Reaction conversion in plug flow reactor was investigated, and experimental results after analysis were compared with batch reactor. The experimental data of both the reactors was fitted to develop second order model. Furthermore, graphical residual analysis was used to validate the model. The initial concentration of sodium hydroxide and ethyl acetate for the hydrolysis reaction in both the reactors were reported to be the significant factors. The maximum conversion of 96% was achieved for a residence/reaction time of five minutes at optimum initial concentrations of sodium hydroxide (0.01mol/L) and ethyl acetate (0.07mol/L) in batch and plug flow reactor.